Public Service Quality in State-Owned Enterprises - Septiawan Ardiputra (International Journal Administration, Business & Organization, 2023)
Public service delivery constitutes one of the fundamental functions of government. In this regard, the presence of public bureaucracy is indispensable for ensuring the effective provision of services to citizens. The government is responsible for providing goods and services needed by the wider public, both through bureaucratic institutions and through State-Owned Enterprises (SOEs). The role of SOEs reflects the mandate of Article 33 paragraph 2 of the 1945 Constitution of the Republic of Indonesia, which stipulates that strategic sectors of production that are vital to the state and affect the livelihood of the public shall be controlled by the state. Accordingly, state control over these strategic sectors is institutionalized through state enterprises. This article employs a library research approach by drawing on relevant documents, books, academic literature, and other secondary sources. As service excellence has long been associated with the institutional image of SOEs, the delivery of high-quality services to customers should become a core principle guiding all service activities. The discussion focuses on the key dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and tangibles.